A work of heart : understanding how God shapes spiritual leaders - McNeal, Reggie (San Francisco : Jossey-Bass, 2011)
'Revised and updated edition of the classic work on spiritual leadership. In A Work of Heart, bestselling author and missional expert Reggie McNeal helps leaders reflect on the ways in which God is shaping them by letting us see God at work in the lives of four quintessential biblical leaders: Moses, David, Jesus, and Paul. McNeal identifies the formative influences upon these leaders, which he sees as God's ways of working in their lives: the same influences at work today forming leaders for ministry in our times. He explores the shaping influence of culture, call, community, conflict, and the commonplace. Offers guidance for church leaders to let God shape their hearts from the inside out Reggie McNeal is the author of the bestselling book Missional Renaissance Gives reassurance for maintaining perspective while doing the demanding work of ministry The book includes illustrative stories of contemporary leaders opening their hearts to God's guidance'--
Includes bibliographical references and index.
Keywords: Christian leadership; RELIGION / Christian Church / Leadership